Treatment of Clubfoot With Ponseti Method Using Semirigid Synthetic Softcast. Issue 47 (November 2015) - Aydin, Bahattin Kerem; Sofu, Hakan; Senaran, Hakan; Erkocak, Omer Faruk; Acar, Mehmet Ali; Kirac, Yunus
Abstract : Abstract: Randomized controlled clinical trial. The main purpose of the present study was to comparatively analyze the effectiveness, advantages, and the complications of using semirigid synthetic softcast with respect to plaster of Paris (POP) during the treatment of clubfoot deformity. The study group consisted of 196 babies (249 feet). A total of 133 feet treated by an orthopedic referral center using semirigid synthetic softcast were included in group A whereas the other 116 feet treated by another orthopedic clinic using POP cast were included in group B. The Pirani scores, number of cast applications, time period until Achilles tenotomy, any skin problems due to the cast itself, and/or cast removal were recorded. A final parent satisfaction score was also obtained. The mean Pirani sores were significantly improved from the first administration to the time before Achilles tenotomy in both groups. There was no significant difference according to the number of casts applied until tenotomy. The slippage of the cast and skin lesions was significantly more common in group B. Higher parent satisfaction levels were detected in group A. Semirigid softcast has been found as superior to POP in the aspects of parent satisfaction and cast-related complication rates.